(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Street lightings is particular critically concerned for the communal authoritie in a developing country because of it strategics importances for the economical & social stabilities. The paper’s main goal is to make roads safer by using an intelligent lighting system that uses less energy. System feature automatically street light brightness adjustment based on the vehicle movements, as well as automatic street light switching ON and OFF based on ambient light. Every given distance, a street light module is put one after the other. The suggested technology also seeks to reduce traffic accidents by identifying whether or not the driver has consumed alcohol. An alcohol sensor module with a skin sensor, breath alcohol sensor, and proximity sensor can be used to do this. The proximity sensor aids in detecting any type of carelessness, while skin sensors & alcohol sensor identify presences of the alcoholic content. Novelty of paper is effectively reducing consumption of energy of the road light by the controlling of intensity of the streets lights, detecting both the human & vehicular movements, and preventing injury and death caused by drunk driving by pre-sensing the alcohol content in drivers in a simple and cost-effective manner. The suggested system may be implemented on a wide scale by the government, and other features can be added in the future, such as a GSM module that can be used to send a notification to the traffic police if the motorist tries to remove the alcohol detection module in any way. In the future, an overspeed detection technology might be combined with street light control.